1973
DOI: 10.1017/s0043174500032513
|View full text |Cite
|
Sign up to set email alerts
|

Periodicity of Germination and Emergence of Some Annual Weeds

Abstract: Seeds of yellow foxtail [Setaria lutescens(Weigel) Hubb.], ivyleaf morningglory [Ipomoea hederacea(L.) Jacq.], common cocklebur (Xanthium pensylvanicumWallr.), jimsonweed (Datura stramoniumL.), velvetleaf (Abutilon theophrastiMedic.), and giant ragweed (Ambrosia trifidaL.) were buried in the soil November 20 and 21, 1966 at Urbana, Illinois for noting emergence of seedlings from April 1 through August 18, 1967. Similarly, seeds of yellow foxtail, ivyleaf morningglory, jimsonweed, velvetleaf, giant ragweed, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
136
2

Year Published

1975
1975
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(150 citation statements)
references
References 16 publications
12
136
2
Order By: Relevance
“…Inhibition of germination due to soil depth has been reported for many species e.g. by Holm (1972), Stoller and Wax (1973), Benvenuti andMacchia (1995, 1997) and Benvenuti et al (2001), including L. rigidum (Gramshaw and Stern 1977). Chauhan et al (2006b) reported that regardless of burial depth, the dormant L. rigidum seed component present at the end of a growing season was quite small (4-16%).…”
Section: Depthmentioning
confidence: 95%
“…Inhibition of germination due to soil depth has been reported for many species e.g. by Holm (1972), Stoller and Wax (1973), Benvenuti andMacchia (1995, 1997) and Benvenuti et al (2001), including L. rigidum (Gramshaw and Stern 1977). Chauhan et al (2006b) reported that regardless of burial depth, the dormant L. rigidum seed component present at the end of a growing season was quite small (4-16%).…”
Section: Depthmentioning
confidence: 95%
“…Spring soil tillage usually results in an increase in emergence of annual broadleaf weeds (Froud-Williams et al 1984;Shilling et al 1986). This increase in weed emergence is often synchronized with crop emergence and is attributed to the strong periodicity of germination in many summer annual weeds (Roberts and Bodrell 1983;Roberts and Lockett 1978;Stoller and Wax 1973) coupled with seed exposure to germination promoters. Spring tillage increases the proportion of seeds that germinate and emerge by exposing weed seeds to germination promoters such as light (Scopel et al 1994), increasing the probable zone of emergence for small-seeded weeds (Mohler and Galford 1997), and reducing the mechanical resistance of the soil to emerging weed seedlings (Morton and Buchele 1960).…”
Section: Introductionmentioning
confidence: 99%
“…Seeds submitted to humid/dry treatments demonstrated a gradual alleviation of dormancy after suspending irrigation (dry substrate) but subsequent increases in dormancy levels once the soil became humid again. A number of workers have shown that seed desiccation followed by rehydration can induce Signalling cyclical dormancy in seeds of tropical species secondary dormancy (Staniforth and Cavers, 1979;Downs and Cavers, 2000), and that periodic changes in soil humidity can affect the dormancy levels of buried seeds (Batlla and Benech-Arnold, 2010) -thus acting as an additional signalling factor for secondary dormancy (Stoller and Wax, 1993;Vleeshouwers, 1997).…”
Section: Discussionmentioning
confidence: 99%